Total Intravenous Anaesthesia with High-Dose Remifentanil Does Not Aggravate Postoperative Nausea and Vomiting and Pain, Compared with Low-Dose Remifentanil: A Double-Blind and Randomized Trial. (3rd June 2014) - Kim, Seong-Hyop; Oh, Chung-Sik; Yoon, Tae-Gyoon; Cho, Min Jeng; Yang, Jung-Hyun; Yi, Hye Ran
Abstract : The study was designed to investigate postoperative nausea and vomiting (PONV) in low- and high-dose remifentanil regimens for total intravenous anaesthesia (TIVA) in adult female patients with American Society of Anaesthesiologists physical status classification I undergoing local breast excision. Propofol and remifentanil 5 ng·mL −1 (L group) or 10 ng·mL −1 (H group) were administered for anaesthesia induction and maintenance. Propofol was titrated within range of 0.1 μ g·mL −1 to maintain bispectral index (BIS) values between 40 and 60. Haemodynamic parameters during the intra- and postoperative periods and 24 h postoperative visual analogue scale (VAS) and PONV were evaluated. Each group with 63 patients was analyzed. The H group showed higher use of remifentanil and lower use of propofol, with similar recovery time. Mean systemic arterial blood pressure (MBP), heart rate, and BIS did not differ significantly before and after endotracheal intubation in the H group. However, significant increases in MBP and BIS were apparent in the L group. Postoperative VAS, PONV incidence and scale, and Rhodes index did not differ significantly between the two groups. In conclusion, TIVA with high-dose remifentanil did not aggravate PONV with similar postoperative pain, compared with low-dose remifentanil. Furthermore, high-dose remifentanil showed more haemodynamic stability after endotracheal intubation. This trial is registered with KCT0000185 .